Strategy of the Tourism, Youth and Sports Office of Padang Pariaman Regency in Optimizing Tourism Promotion - Lasmi, Ami; Efi , Agusti (Amalee: Indonesian Journal of Community Research and Engagement, 2025)
Competition in the global tourism industry requires regions to create innovative and competitive promotional strategies. Padang Pariaman Regency, through the Department of Tourism, Youth, and Sports, utilizes the presence of tourism ambassadors as promotional agents to introduce the potential of local destinations. The purpose of this activity was to analyze the promotional strategies implemented through the role of tourism ambassadors and evaluate their effectiveness and contribution to increasing tourist visits. The method used was a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. Data were analyzed using a SWOT approach to identify strengths, weaknesses, opportunities, and threats in strategy implementation. The results showed that tourism ambassadors have played an active role in promotions, both directly and through digital media, but their role is still limited to symbolic aspects and is less than optimal in creating informative promotional content. The conclusion of this activity indicates that the promotional strategy through tourism ambassadors has great potential for development by increasing communication capacity, content creativity, and stronger collaboration between the department and ambassadors. The impact of this activity is expected to improve the image of regional tourism, expand the reach of tourist destination information, and strengthen the role of the younger generation in sustainable tourism development.